Effects of herbage ingestion upon ileal digestibility of amino acids in heavy Iberian pigs fed on an acorn-based diet - Garcia-Valverde, R.; Nieto, R.; Aguilera, J. F. (JOURNAL OF ANIMAL PHYSIOLOGY AND ANIMAL NUTRITION, 2010)
P>We conducted two experiments with heavy Iberian pigs to determine the ileal digestibility of amino acids (AA) in acorns and freshly cut herbage, and the effects of adding fresh herbage upon the supply of ileal digestible AA when pigs were fed on holm-oak acorns. In Experiment 1, carried out in cannulated pigs of 107 kg bodyweight (BW), daily intake of acorns reached 44.9 g DM/kg0.75 BW. Arg, His and Thr showed the lowest apparent ileal digestibility (AID) values, whereas Met, the branched-chain AA and Phe had the highest coefficients. The AID of total EAA was 0.716 but only 0.222 for NEAA. Most of the digestive and absorptive processes of acorn protein occurred before the hindgut. Acorn provides (per kg DM) 2.27 g apparent ileal digestible Lys and 22.7 g apparent total digestible AA. Standardized ileal digestibility (SID) values for EAA, NEAA and total AA were 0.924 +/- 0.020, 0.784 +/- 0.041 and 0.860 +/- 0.029. In Experiment 2 fresh herbage was given to six cannulated Iberian pigs of 140 kg either as a single feed (13.7 g DM/kg0.75 BW) or as a supplement to acorns (28.4 g DM/kg0.75 BW). When only freshly cut forage was offered the AID of the EAA, NEAA and total AA was close to 0.65 and supplied (per kg DM ingested) 5.61 g AID Lys and 91.7 g digestible AA. Standardized ileal values were 0.744 +/- 0.023, 0.912 +/- 0.038 and 0.831 +/- 0.030 respectively. The addition of fresh forage to the acorns led to a significant decrease in AID of AA in acorn due to digesta transfer to the hindgut: His (p < 0.01), Met (p < 0.001), Phe (p = 0.092), Thr (p < 0.05) and Val (p < 0.05), but Arg, Lys and the branched-chain AA remained unaffected. The main contribution of herbage to AA nutrition of the grazing Iberian pig relies mainly on increasing the supply of digestible AA for pig tissues.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL PUBLISHING, INC
Keywords: acorns; amino acids; digestibility; herbage; iberian pig

Amino acid availability and energy value of acorn in the Iberian pig - Aguilera, J. F.; Nieto, R.; Rivera, M.; Garcıa, M. A. (Livestock Production Science, 2002)
Two experiments have been performed to determine amino acid digestibility and energy value of acorn (Quercus rotundifolia L.) for Iberian pigs. In experiment 1 ileal digestibility of amino acids was determined in ﬁve ileum-cannulated growing pigs fed whole ground acorn. An estimation of endogenous protein losses was carried out by feeding a protein-free diet, added (180 g/kg) or not with acorn hulls. True ileal digestibility of all essential amino acids measured was high (0.798–1.03) except for arginine (0.523), lysine (0.601), isoleucine (0.760), leucine (0.777) and phenylalanine (0.716). The average value for the digestibility of the sum of amino acids was 0.664. Lysine was the ﬁrst limiting amino acid compared with the amino acid proﬁle of the ideal protein for pigs. In experiment 2, total tract digestibility of nutrients and N balance were determined in ﬁve, non-cannulated pigs offered whole acorns. High coefﬁcients for the apparent total tract digestibility of dry matter (ApDM) (0.830) and energy metabolizability (ME/GE; 0.805) were found. ME content for acorn kernel was 16.6 MJ/kg DM, while the apparent total tract digestibility of total N (ApTN) was as low as 0.408. However, a positive N retention was observed (3.7 g/day). Comparing experiments 1 vs. 2, inclusion of acorn hulls resulted in a marked decrease in DM intake, ApTN and in N retention (25.1 g/day, in total tract data from experiment 1). The negative effects of acorn hulls on protein digestibility and N balance were corroborated in rats given similar amounts of either whole ground acorn or ground acorn kernel. Dietary supplementation with lysine is proposed to achieve a higher efﬁciency of protein accretion in the Iberian pig when fed on acorn.
Keywords: acorn; amino acids; energy value; pig-feeding and nutrition; protein quality